Ask your own question, for FREE!
Mathematics
OpenStudy (anonymous):

y=2x+5y=3x-3

OpenStudy (anonymous):

ok, if the given sequences of equations is correct, then y=3x-3, you can substitute for y in the this equation: y=2x+5y (3x-3)=2x+5(3x-3) => (3x-3) = 2x + 15x - 15 3x-3 = 17x -15 14x = 12 x = 12/14 now you can substitute back in the equation y=3x-3

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!